Firms’ FDI ownership: The influence of government ownership and legislative connections - Pan, Yigang; Teng, Lefa; Supapol, Atipol Bhanich; Lu, Xiongwen; Huang, Dan; Wang, Zhennan (Journal of International Business Studies, 2014)
The level of ownership in an overseas subsidiary has been an important issue in international business. Existing literature, based on transaction cost theory, predicts that firms prefer higher ownership for subsidiaries located in favorable foreign institutional environments. We propose two moderating factors to this prediction: governments as owners of firms and firms’ legislative connections. We hypothesized that the level of subsidiary ownership was less affected by the heterogeneity of foreign institutional environments for firms with a higher level of government ownership and for firms with legislative connections. These two interaction effects were tested using a sample of overseas subsidiaries documented in the 2010 annual reports of listed Chinese firms. The empirical findings provide robust support for the hypothesized effects. This study offers fresh insight on the role of government and political factors in firms’ internationalization activities.